(Sin alpha)^2 + (Cos alpha)^2 = 1 | *2 years 44 weeks* ago | jscottb | 2013-06-27 16:23 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *3 years 3 weeks* ago | birdmun | 2013-04-11 12:51 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *3 years 32 weeks* ago | kariloy | 2012-09-20 20:03 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *4 years 5 weeks* ago | kingart3 | 2012-03-29 21:10 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *4 years 13 weeks* ago | zenrascal | 2012-02-06 00:03 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *5 years 23 weeks* ago | saurabh pandey | 2010-11-24 20:39 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *5 years 36 weeks* ago | rugcommunity | 2010-08-22 16:10 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *6 years 1 week* ago | Kikez | 2010-04-27 03:51 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *6 years 11 weeks* ago | hari | 2010-02-13 16:23 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *6 years 26 weeks* ago | mcx | 2009-11-04 23:03 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *6 years 26 weeks* ago | TheGrue | 2009-11-02 00:27 | *6 years 31 weeks* ago |

(Sin alpha)^2 + (Cos alpha)^2 = 1 | *6 years 27 weeks* ago | Prettybird | 2009-10-30 02:35 | *6 years 31 weeks* ago |